PEMBERDAYAAN PETANI DAN EDUKASI HUKUM DAGANG DALAM PEMASARAN PRODUK AGRIBISNIS BERKELANJUTAN - Pratama, Triyan Bayu; Kurniawan, Nando Dwi; Rahman Wiyono, Agung Abdul (Jurnal Pengabdian Masyarakat Sabangka, 2025)
Empowering farmers in Ketapang Village, Kademangan District, Probolinggo City, has become one of the areas with considerable agribusiness potential, both in terms of natural resources and labor. A lack of legal understanding weakens farmers' bargaining position when dealing with other business actors, while limited digital literacy hinders access to wider markets. This community service activity aims to empower farmers through education on trade law and training in sustainable agribusiness product marketing. The method used is Participatory Rural Appraisal (PRA), which actively involves farmers in problem identification, training, mentoring, and evaluation. The results of the activity show a significant increase in farmers' understanding of trade law, farm management skills, and digital and sustainable marketing strategies. Thus, this activity contributes to the creation of a fair, competitive, and sustainable agricultural system, in line with the Sustainable Development Goals (SDGs).